Assessment of inflammatory markers and periodontal outcomes in CKD patients with periodontitis - Rahman, Nurul Aliya Abdul (2022)
Chronic kidney disease (CKD) and periodontitis have an impact on patient’s morbidity and mortality. The prevalence of comorbid CKD and periodontitis is shown to be frequent. Periodontitis increases the inflammatory burden, which has been shown to disrupt renal function by altering serum inflammatory levels, and potentially worsening CKD. Pro-inflammatory Interleukin-1 (IL-1) and anti-inflammatory Interleukin-10 (IL-10) have immunomodulatory properties that regulates host immune responses. Little is known about changes in the serum inflammatory markers of IL-1 and IL-10 following the periodontal therapy in CKD patients in our populations. Therefore, this study was aimed to assess and compare the levels of inflammatory markers IL-1 and IL-10 as well as periodontal parameters at baseline and after receiving NSPT. Twenty CKD patients (stage 3 and stage 4) with periodontitis (Group 1), twenty non-CKD patients with periodontitis (Group 2) and twenty healthy patients (Group 3) were selected. The dental parameters such as Periodontal Probing Depth (PPD), Clinical Attachment Loss (CAL), Gingival Bleeding Index (GI) and Plaque Score (PS) were measured in each patient during first visit (baseline) and six weeks later (second visit). Blood sample was collected during each visit and analysed for serum IL-1 and IL-10 concentration using Enzyme-Linked Immunosorbent Assay. Our findings shows that IL-1 and IL-10 levels were found significantly higher (p<0.05) in CKD patients with periodontitis (Group 1) as compared to non-CKD patients with periodontitis (Group 2) and healthy subjects (Group 3). When compared to other groups, the levels of dental parameters (PPD, PS and GBI in Group 1 were significantly higher (p<0.05). Following NSPT, there was significant reduction (p<0.05) in inflammatory markers and clinical periodontal parameters in Group 1 and Group 2. This study demonstrates that patients with CKD and periodontitis had a more severe systemic inflammatory response and poorer periodontal status than non-CKD. NSPT shown improvement in both inflammatory markers and dental parameters as well as delay the progression of CKD. IL-1 and IL-10 is a promising inflammatory marker to assess CKD progression. Therefore, multicentre and larger sample size studies are needed in the future.